Damping of javelin vibrations in flight - Hubbard, M.; Laporte, S. (Journal of Applied Biomechanics, 1997)
Javelin vibrations in flight are caused by large forces applied transversely to the javelin's long axis during its acceleration. These decay throughout the early portion of the flight but can have substantial effects on aerodynamic lift and drag forces. Vibration decay is due to two main factors: aerodynamic dissipation and material, or hysteretic, damping. The relative contributions of these two factors are identified using theoretical models and laboratory experiments. With models for vibration decay, flight simulations can include realistic, if hypothetical, vibrational effects on the achievable range.